2018
DOI: 10.3390/ma11091537
|View full text |Cite
|
Sign up to set email alerts
|

High Electrochemical Performance of Nanotube Structured ZnS as Anode Material for Lithium–Ion Batteries

Abstract: By using ZnO nanorods as an ideal sacrificial template, one-dimensional (1-D) ZnS nanotubes with a mean diameter of 10 nm were successfully synthesized by hydrothermal method. The phase composition and microstructure of the ZnS nanotubes were characterized by using XRD (X-ray diffraction), SEM (scanning electron micrograph), and TEM (transmission electronic microscopy) analysis. X-ray photoelectron spectroscopy (XPS) and nitrogen sorption isotherms measurements were also used to study the information on the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Besides, pure ZnS suffers from volume expansion during the charge/discharge cycle and poor cyclic and rate performance. 87 On the other hand, ZnS performed well as corrosion inhibiter in 1 M HCl for mild steel. 88 ZnS has tremendous potential for supercapacitors because of its tunable electronic properties and high thermal and rich redox kinetics.…”
Section: Why Zinc Sulfide (Zns)?mentioning
confidence: 98%
See 1 more Smart Citation
“…Besides, pure ZnS suffers from volume expansion during the charge/discharge cycle and poor cyclic and rate performance. 87 On the other hand, ZnS performed well as corrosion inhibiter in 1 M HCl for mild steel. 88 ZnS has tremendous potential for supercapacitors because of its tunable electronic properties and high thermal and rich redox kinetics.…”
Section: Why Zinc Sulfide (Zns)?mentioning
confidence: 98%
“…ZnS is regarded as a promising alternative to carbon as anode material for lithium-ion batteries due to its high theoretical capacity. Besides, pure ZnS suffers from volume expansion during the charge/discharge cycle and poor cyclic and rate performance . On the other hand, ZnS performed well as corrosion inhibiter in 1 M HCl for mild steel .…”
Section: Zinc-based Supercapacitor Materialsmentioning
confidence: 99%
“…Additionally, previous research has indicated that ZnS undergoes a combined conversion-alloying reaction during cycling, resulting in a large irreversible volume change. 6 Numerous efforts have been dedicated to enhancing the lithium storage performance of ZnS, employing various strategies such as nanostructural design, 7 heterostructure building 8 and combination with carbonaceous materials. 9 Prominently, the modification of nanoscale ZnS with a carbon matrix has shown great promise in mitigating the pulverization process during cycling.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36] For example, Zhang et al prepared ZnS nanotubes using ZnO nanorods as a template, which exhibit a capacity of 950 mA h g À1 at 0.1 A g À1 and good cycling performance when evaluated as anodes for LIBs. 37 Compared to the rational structure design, the hybridization with conductive carbonaceous materials was considered as more effective and wider used strategy for enhancing the electrochemical performance of the ZnS anode. [38][39][40][41] For example, Liu et al prepared pitaya-like ZnS/ carbon nanospheres as a LIB anode, which benefitted from the dual-carbon being able to accommodate the volume expansion in the cycling process.…”
Section: Introductionmentioning
confidence: 99%